PROBLEMS OF GROUP DYNAMICS IN PROBLEM BASED LEARNING SESSIONS - Ahmed, Zafar (Journal of Ayub Medical College Abbottabad, 2014)
Background: Beneficial effects of Problem Based Learning (PBL) in medical education are often emphasized. However, there is another side of the coin. This study was conducted to find out frequency of PBL group problems in our setup and the influence of these problems on students' learning. We also compared the perception of students and tutors as regard to frequency and level of hindrance caused by these problems in PBL sessions. Methods: This cross sectional study was conducted at Foundation University Medical College, Islamabad. 100 students of 3rd year MBBS of 2011 and their 17 PBL tutors were asked to fill a questionnaire. They were asked to rank the factors according to frequency (perceived frequency) and according to the level of hindrance to learning these factors are causing. All data was entered and analysed using SPSS-12. Results: Students ranked Dominant student as the most important problem and Psychosocial factors as the least important problem. Tutors ranked Quiet student as the most important problem and Personality clash as the least important factor. Student's ranked Dominant student as the problem causes most hindrance and Quiet student as the problem causing least hindrance. Tutors ranked Lack of commitment as the problem causing most hindrance and Personality clash as the problem causing least hindrance. There was good agreement between the students and the tutors on all the factors regarding important problem except Lateness, absenteeism (p=0.04) and Personality clash (p=0.001).Similarly there was good agreement between the students and the tutors on all the factors regarding hindrance except Lack of commitment (p= 0.015) and Personality clash (p=0.023). Conclusion: The present study showed that from both students' and tutors' perspectives, the ranking of most important problems that can disturb PBL session function and the level of hindrance they cause were statistically similar for majority of the problems. Keywords: Problem-based learning, tutorial group problems, teachers'/students' perceptions, group's dysfunction, problems' frequency/importance